Efficacy of Rational Emotive Behaviour Therapy on Religious Intolerance Among Adolescents in Taraba State, Nigeria - Moses Godswill Alhassan; Muhammad Ahmad Baba (Interdisciplinary Journal of Education)
Religious intolerance poses significant threats to social cohesion and peaceful coexistence, particularly in multi-religious regions like Wukari Education Zone of Taraba State, Nigeria. This study examined the efficacy of Rational Emotive Behaviour Therapy (REBT) in addressing cognitive, emotional, and behavioural dimensions of religious intolerance among adolescents. A quasi-experimental one-group pre-test post-test design was employed, involving 20 SS1 students selected using purposive sampling. Data were collected using an adapted Religious Intolerance Scale (RIS) and analyzed with paired and independent t-tests. Findings revealed that REBT significantly reduced cognitive distortions, negative emotions, and irrational behaviours associated with religious intolerance. Furthermore, no significant gender differences were observed in the efficacy of REBT, indicating equal effectiveness for male and female adolescents. The study concludes that REBT is an effective therapeutic intervention for reducing religious intolerance and promoting interfaith tolerance among adolescents.